IMPLEMENTASI MODEL PEMBELAJARAN COOPERATIVE TIPE NUMBER HEAD TOGETHER DALAM MENINGKATKAN PRESTASI BELAJAR PAK SISWAKELAS VIII SMP NEGERI 2 SALUPUTTI - Juniati Tangibali; Natasia Irene; Alfriyanti (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This research is about the Implementation of the Number Head Together Type of Cooperative Learning Model in Improving Cristian Religious Education Learning Achievement of Class VIII Students of SMP Negeri 2 Saluputti". The background of this research is the decline in student achievement both from the cognitive, affective and psychomotor aspects due to the lack of student action in learning. Thus, this study aims to improve student achievement with cooperative learning model Number Head Together. The type of research method used in this research is Classroom Action Research (CAR). The research subjects are class VIII C students, totaling 30 students at SMPN 2 Saluputti. This research was conducted in two cycles. The results showed an increase in student learning achievement from the first cycle in general in the cognitive aspect 23%, affective 23% and psychomotor 37%. And in the second cycle the cognitive aspect increased to 90%, affective 90% and psychomotor 87%. Thus, it can be concluded that the Number Head Together model in learning can improve learning achievement.